An imaged 15 MJup companion within a hierarchical quadruple system - Chomez, Antoine; Squicciarini, V.; Lagrange, A.-M.; Delorme, P.; Viswanath, G.; Janson, M.; Flasseur, O.; Chauvin, G.; Langlois, M.; Rubini, P.; Bergeon, S.; Albert, D.; et al. (Astronomy and astrophysics, 2023)
Since 2019, the direct imaging B-star Exoplanet Abundance STudy (BEAST) at SPHEREVLT has been scanning the surroundings of young B-type stars in order to ascertain the ultimate frontiers of giant planet formation. Recently, the Myr HIP 81208 was found to host a close-in (∼50 au) brown dwarf and a wider (∼230 au) late M star around the central 2.6 M⊙primary. Alongside the continuation of the survey, we are undertaking a complete reanalysis of archival data aimed at improving detection performances so as to uncover additional low-mass companions.